Firms’ capital structure decisions: The role of top management characteristics - Bsoul, Ruba; Odat, Mahmoud; Atwa, Rawan (International Journal of Management and Sustainability, 2025)
Firms’ capital structure greatly impacts their overall performance and value and the return and risk associated with shareholders. The upper echelons theory argues that CEOs’ managerial role, mainly decision-making is largely affected by their functional and personal characteristics. This research aims to investigate the role of CEOs’ demographic attributes in firms’ capital structure decisions based on this theory. The analysis is based on a sample of 80 non-financial firms listed on the Amman Stock Exchange (ASE) for the period 2015 - 2022. The attributes examined include age, ownership, qualification, duality, experience, and tenure. We use the book-value-based debt ratio to measure capital structure. The analysis confirms a significant negative impact for ownership and experience on capital structure and a significant positive impact on duality and tenure. However, firms’ capital structure is found to be unrelated to CEOs’ age and qualifications. The results provide crucial insights for companies in appointing decision-makers and the need to align more closely with international governance standards, which can enhance firm performance and sustainability.